Sustainability Focus in Destination Management. The Case of Russia - DEDUSENKO, Elena Aleksandrovna; WAGENSEIL, Urs (Journal of Environmental Management and Tourism, 2020)
This paper analyzes the tourism management regarding sustainability of eight Russian regions and discusses the possibility of implementing the principles of sustainable tourism development in a particular region using the performance criteria of the Global Sustainable Tourism Council (GSTC). The goals of this paper are to focus on sustainable tourism development as a function of destination management and discuss the problems of the integrated efforts of Destination Management Organizations (DMOs) in the field of tourism and destination sustainability.